2018
DOI: 10.3892/ijmm.2018.3842
|View full text |Cite
|
Sign up to set email alerts
|

ISL1 promotes cancer progression and inhibits cisplatin sensitivity in triple-negative breast cancer cells

Abstract: Triple-negative breast cancer (TNBC) is a type of breast cancer that is characterized by the lack of expression of estrogen and progesterone receptors, and epidermal growth factor receptor 2. Therefore, there is an absence of a specific target for effective therapy in TNBC. Cisplatin is usually employed as a first-line chemotherapy agent for patients with TNBC. However, resistance remains an obstacle for cisplatin-based chemotherapy, due to its elusive underlying mechanism. Previously, abnormal expression of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…SE regulators are known to act cooperatively (Hnisz et al, 2013;Lové n et al, 2013;Whyte et al, 2013) and likely do so also with ISL1, which may explain some of the inconsistent observed effects in the CRISPRi/a systems. A role of ISL1 in therapy resistance has been suggested in triple-negative breast cancer (TNBC) cells, in which ISL1 overexpression inhibits cisplatininduced cell apoptosis (Zhang et al, 2018). Other developmental transcription factors are also known to participate in cell survival in cancer cells, collectively known as ''lineage survival'' oncogenes, e.g., MITF (Garraway et al, 2005) and NKX2.1, SOX2, and CDX2 (Bass et al, 2009;Salari et al, 2012;Weir et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…SE regulators are known to act cooperatively (Hnisz et al, 2013;Lové n et al, 2013;Whyte et al, 2013) and likely do so also with ISL1, which may explain some of the inconsistent observed effects in the CRISPRi/a systems. A role of ISL1 in therapy resistance has been suggested in triple-negative breast cancer (TNBC) cells, in which ISL1 overexpression inhibits cisplatininduced cell apoptosis (Zhang et al, 2018). Other developmental transcription factors are also known to participate in cell survival in cancer cells, collectively known as ''lineage survival'' oncogenes, e.g., MITF (Garraway et al, 2005) and NKX2.1, SOX2, and CDX2 (Bass et al, 2009;Salari et al, 2012;Weir et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…47 Islet-1 overexpression was reported to reduce TNBC cell response to cisplatin. 47,48 In the cells that have limited response to cisplatin, the role of TMEPAI is not prominent.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with normal tissues, ISL1 is significantly upregulated in various cancers. ISL1 is involved in caner progression and is considered as a prognostic factor of multiple cancers [ 11 18 ]. In this study, we identified ISL1 as a novel oncogene acting through activation of PI3K/AKT signaling pathway in NB.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ISL1 has been reported to play crucial roles in cancer progression, and this is mainly based on an aberrant expression of ISL1. ISL1 was involved in triple-negative breast cancer, melanoma, and gastric cancer progression [ 11 13 ], and it was highly expressed in non-Hodgkin lymphoma compared to normal lymph nodes or Hodgkin lymphoma [ 14 ]. Besides, ISL1 was also verified to be a novel regulator of the cyclin D1 and c-Myc genes in cancer [ 15 ], and it could predict prognostics for cancers like gastric cancer, bladder cancer, and may also act as a biomarker in NB [ 13 , 16 18 ].…”
Section: Introductionmentioning
confidence: 99%